(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Give This research article delves into the thermal stability of succinite -an organic polymer- when amalgamated within the structure of PA6 nanofibers, with a focus on assessing the consequent mechanical and structural performance of such composite nanofibers. The electrospinning method employed, involves the process of heating and high voltage to polymers, is known to inherently alter their thermal properties. The primary objective of this study is to examine the thermal stability of succinite within the PA6 nanofiber matrix and to evaluate the preservation of the composite material's mechanical and structural integrity, particularly under varying PA6 concentrations (16%, 20%, and 28%). Through thermal analysis techniques such as Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA), and Infrared (IR) spectroscopy, it was observed that the succinite nano powder (ranging from 5-20 nm) exhibits minimal loss of volatile components, notably the NH amino group, upon heating to 150 ºC—a common solvent temperature during suspension preparation. This loss does not surpass 0.1% of the original volume, ensuring the predominance of critical components like succinite acid (C4H6O4) in the composite. Furthermore, PA6 nanofibers were fabricated with varying PA6 polymer percentages (16%, 20%, and 28%) and with or without the integration of succinite nano powder, to compare mechanical properties. It was noted that incorporating succinite into PA6 nanofibers (at 16% concentration) led to an increase in fibre diameter to 78±14 nm from the 60±17 nm diameter of pure PA6 fibres, alongside a notable decrease in elastic modulus by approximately 2.3 times. However, the ultimate tensile strength only marginally reduced from 295.2 MPa to 274.9 MPa, with a slight decrease in toughness from 168.3 to 162 MPa. Contrary to pure PA6 fibres, the strain-to-failure ratio for the composite nanofibers saw an approximate 7% increase. This study elucidates the subtle yet significant modifications in the mechanical and structural properties of polymer composites attributable to their thermal stability. These findings furnish vital insights for the application of such composite materials in diverse thermal management contexts, particularly when utilised as protective materials.